Advocacy to provide good quality oncology services during the COVID-19 pandemic – Actions at 3-levels. (August 2020) - Lee, Anne W.M.; Xu, Zhi-Yuan; Lin, Lily; Xu, Joy; Yang, Jin; Lee, Eric; Hui, Tim; Cheung, Jacob
Abstract: The COVID-19 pandemic is a devastating catastrophe to the whole world, China is the first country seriously affected. This review shows that it is possible to stop wide-spread infection in the country and to provide good quality oncology services even during this challenging period, through concerted efforts with well-organized actions at all levels (National/Municipal, Hospital and Department). The key strategies leading to successful impacts are summarized for sharing. In addition to making practice changes to cope with the adverse realities, oncologists should also work together to raise pragmatic suggestions to policy makers and be strong advocates to protect our patients from the detrimental effect of delay or compromised treatment.